2011
DOI: 10.1111/j.1348-0421.2011.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of prior influenza infection on alveolar macrophage phagocytosis of Staphylococcus aureus and Escherichia coli: involvement of interferon-gamma production

Abstract: The influenza A virus is one of the main causes of respiratory infection. Although influenza virus infection alone can result in pneumonia, secondary bacterial infection combined with the virus is the major cause of morbidity and mortality. Interestingly, while influenza infection increases susceptibility to some bacteria, including Streptococcus pneumoniae, Staphylococcus aureus (S. aureus), and Haemophilus influenzae, other bacteria such as Escherichia coli (E. coli) and Klebsiella pneumoniae are not associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Furthermore, treatment of non-virus infected mice with exogenous IFN-γ can mimic viral infection and result in inhibition of alveolar macrophage-mediated bacterial phagocytosis (3). A critical role for IFN-γ in inhibiting phagocytosis of S. aureus by alveolar macrophages has similarly been reported (43). Further experiments showed that the relatively high levels of IFN-γ in the lung following influenza caused inhibition of MARCO expression (3), the scavenger receptor necessary for recognition of non-opsonized pneumococci by alveolar macrophages (44).…”
Section: Influenza-induced Suppression Of Antibacterial Innate Immunitymentioning
confidence: 74%
“…Furthermore, treatment of non-virus infected mice with exogenous IFN-γ can mimic viral infection and result in inhibition of alveolar macrophage-mediated bacterial phagocytosis (3). A critical role for IFN-γ in inhibiting phagocytosis of S. aureus by alveolar macrophages has similarly been reported (43). Further experiments showed that the relatively high levels of IFN-γ in the lung following influenza caused inhibition of MARCO expression (3), the scavenger receptor necessary for recognition of non-opsonized pneumococci by alveolar macrophages (44).…”
Section: Influenza-induced Suppression Of Antibacterial Innate Immunitymentioning
confidence: 74%
“…In investigating this discrepancy, authors noted the increase in IFNγ concentrations following influenza A infection, and found that macrophage phagocytosis of varied bacterial strains was differentially affected by the presence of IFNγ. IFNγ inhibited macrophage phagocytosis of the gram-positive bacterium Staphylococcus aureus but failed to inhibit phagocytosis of the gram-negative pathogen E. coli (34). In accordance with other studies (15), this suggests that high IFNγ concentrations following influenza infection may contribute to hyper-susceptibility to S. pneumoniae infection by inhibiting bacterial phagocytosis by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, airways can be blocked by a foreign object or tumors that prevent the alveolar sacs from filling with air and collapse of lung tissue can occur in the affected area. Influenza viruses are among those foreign objects that cause alveolar sac closure and they are among the most common factors that lead to human respiratory infections and cause high morbidity and mortality rate [11]. Salmon et al [12] investigated the influence of airway closure and alveolar collapse on transpulmonary pressure-volume curves under large-volume deflation and inflation.…”
Section: Introductionmentioning
confidence: 99%